Health behaviors predicting risk of obesity in US adults: What does a healthy lifestyle look like? - Jacqueline A. Vernarelli; Jessica R. Kiel; Christopher D. Coleman; Satya S. Jonnalagadda (Wiley, 2024)
Abstract Objective The purpose of this study was to examine the association between lifestyle factors and body weight in a nationally representative sample of US adults and to evaluate the association between a novel "Healthy Habits Composite Score (HHCS)" and risk of obesity. Methods This cross‐sectional study included data from 4870 adults who participated in the 2017-2018 National Health and Nutrition Examination Survey (NHANES). The HHCS was developed based on 4 factors: diet, physical activity, sedentary time, and sleep, all of which were measured during the NHANES. A "healthy lifestyle" was defined as meeting ≥3 of the 4 established criteria. Data analysis was conducted using SAS 9.4 and procedures to account for the complex survey design. All models were adjusted for age, sex, race, household income, and education. Results Adults with obesity had significantly lower dietary quality (48.8 ± 0.6 vs. 53.2 ± 0.9) and reported significantly more sedentary time (∼1 h more; 356.3 ± 7.0 vs. 301.4 ± 8.3 min) than lean adults, both p < 0.001. Achieving a healthy lifestyle based on the HHCS was associated with nearly double the odds of having a healthy body weight (OR 1.9, p < 0.001). Conclusions Following a lifestyle focused on healthy habits (diet quality, physical activity, limited sedentary time, and sleep) was strongly associated with a decreased risk of obesity: an individual who achieved three or more healthy habits had nearly twice the odds of having a healthy body weight. Therefore, comprehensive interventions that address and promote a wide range of healthy habits may be most effective for lowering obesity risk.